Herbal Identification and its Benefits using Production Rules Approach - Roslina, Abd. Hamid; Nor Azhar, Ahmad; Rahmah, Mokhtar; Fauziah, Zainuddin; Hester Liong, King Huat (Faculty of Computer Systems & Software Engineering, Universiti Malaysia Pahang, 2016)
Expert System on defining herbs, using Production Rules is the system will solve a problem of using conventional procedures. By using physicals structure, identifying herbs is not too difficult. Moreover, it can provide a list of herb benefits focusing herbs in Malaysia. Rule-based derived from the rules for herbs knowledge domain. Thus, the system can learn from its experience by using factual knowledge based. The system has the capability to derive new case on new findings. Therefore, this system will help to identify herbs easier. This system also can be implemented in others knowledge domain.